SimCoach Evaluation - Meeker, Daniella; Cerully, Jennifer L.; Johnson, Megan D.; Iyer, Neema; Kurz, Jeremy R. (RAND Corporation, 2023)
This report describes RAND Corporation researchers’ assessment of SimCoach, a computer program featuring a virtual human that speaks and gestures in a video game–like interface, designed to encourage service members, especially those with signs or symptoms of posttraumatic stress disorder or depression, to seek help for psychological health concerns.